Asymmetric synthesis of furofurans - Manat Pohmakotr (2018)
© 2017 Elsevier Ltd Furofurans are one of the largest sub-types of classical lignans which have been found to possess a broad range of important biological activities. Tremendous efforts have been directed to develop synthetic methodologies for the synthesis of furofurans, especially in a stereoselective manner, due to their interesting bioactivities associated with the structural and stereochemical complexity. This article summarizes the reports on asymmetric synthesis of furofurans disclosed during the period of 2004–2017.